Ductile–Brittle Transition Mechanism and Dilute Solution Softening Effect of Body-Centered Cubic Metals - Jie Zhang; Tianliang Zhao; Tingping Hou; Yan Li; Kaiming Wu (Metals, 2025)
Body-centered cubic (BCC) metals, extensively utilized in low-alloy high-strength steels and heat-resistant alloys, exhibit a pronounced ductile–brittle transition (DBT) at cryogenic temperatures, marked by a well-defined yet narrow ductile–brittle transition temperature (DBTT) window. This paper overviews the research progress regarding the DBT mechanism of BCC metals. This mechanism was recently found to be related to the mobility of screw dislocation relative to edge dislocation, a decrease in which can induce a critical drop in the proliferation efficiency of dislocation sources. Furthermore, this paper summarizes the current research on the dilute solution softening effect of BCC metals, which has been frequently observed and studied in refractory alloys. The mechanism of this effect involves the low-temperature mobility of screw dislocations that could be promoted by specific solute atoms through kink pair nucleation. This offers a potential strategy for reducing the DBTT of low-alloy steels using a dilute solution, namely microalloying in metallurgy. However, the current understanding of the relationship between the macroscopic ductility of BCC alloys and the dilute solution softening effect is limited. This review aimed to draw attention to this relationship and strengthen related research.